The role of corporate saving over the business cycle: Shock absorber or amplifier? - Xiaodan Gao; Shaofeng Xu (Bank of Canada, 2018)
We document countercyclical corporate saving behavior with the degree of countercyclicality varying nonmonotonically with firm size. We then develop a dynamic stochastic general equilibrium model with heterogeneous firms to explain the pattern and study its implications for business cycles. In the presence of financial frictions and fixed operating costs, a persistent negative productivity shock signals low future income and prompts firms to hold more cash in order to preserve financial flexibility and maintain normal operations. This countercyclicality exhibits a hump-shaped relation to firm size. Compared with mediumsized firms, small firms have a higher marginal product of capital and thus better investment opportunities, which compete for resources with cash, while large firms have more pledgeable assets and demand less cash. We find that, on average, firms accumulate cash by cutting investment and employment in recessions, which reduces aggregate output and increases economic fluctuations. Corporate saving, therefore, amplifies aggregate shocks.
Keywords: E20; E22; E32; G31; G32; 330; Business fluctuations and cycles; Economic models